Assessment of a novel unidirectional mid-term absorbable barbed suture versus a competitor barbed suture for vaginal cuff closure after gynaecology surgery, study protocol of a randomized controlled trial - BARHYSTER - Petra Baumann; Lourdes Hinojosa Sánchez; Núria Grané Garcia; Larisa Sologiuc; Amadeus Hornemann (BMC Surgery)
Abstract Background Total laparoscopic hysterectomy (TLH) is nowadays the standard to treat benign and malignant disease occurring in the uterus, but the number of robotic-assisted surgeries is increasing worldwide. To facilitate the handling of sutures in a bi- and tri-dimensional plane, a new type of suture material has been developed, named barbed sutures, which are in use in different indications. In comparison to conventional suture materials, the barbs anchor the suture in the tissue, provide tissue approximation and prevent slippage without the need for knot tying. Several meta-analyses and systematic reviews have shown that they are safe and efficient. The current study investigates the clinical outcome of a novel unidirectional mid-term absorbable barbed suture which differs in its configuration from other barbed sutures. The collected data will be prospectively compared to the results of a competitor’s unidirectional mid-term absorbable barbed suture and retrospectively to the findings reported for conventional sutures after hysterectomy in the literature. Methods An international, randomised, multicentric, single-blinded design was chosen. A total of 132 patients will be included receiving randomly either the novel unidirectional barbed suture versus the competitor unidirectional barbed suture in a 3:1 ratio. Both suture materials will be applied to close the vaginal cuff after laparoscopic hysterectomy and the time for suturing is the primary endpoint. As secondary objectives, the following parameters will be collected and compared in both suture groups: intraoperative handling of the suture material, quality of life using the Female Sexual Function Index (FSFI), patient satisfaction, pain, and complications occurring in the short-term and long-term follow-up. For each patient, the study lasts 6 months after surgery. Discussion This study will assess the clinical performance of a novel unidirectional mid-term absorbable barbed suture material for the first time in gynaecology surgery and, to our knowledge, it will be the second largest RCT performed so far in total laparoscopic hysterectomy using unidirectional mid-term absorbable barbed suture materials. Trial registration The study was prospectively registered before the enrolment of the first patient. Registration was performed under www.clinicaltrials.gov , NCT 06024109. Registered on 15 August, 2023.